Politološka interpretacija Magne Carte - Spruk, Jure (Teorija in praksa, 2020)
The article considers how one of the most important documents in history - Magna Carta Libertatum - is understood politically. The author places the document's origin in the context of the monarch's tendency to arbitrarily reach into the private property of the nobility, triggering a political process of rearranging the constellation of political power in English society. Contextualisation of the document shows that the rebellious nobility's demands did not include any revolutionary rearrangements of the equilibrium between the political power held by the king and the nobility, although by clearly referring to the "good" old law their intention was to formally reestablish the equilibrium that was in place hundreds of years before. In their nature, these claims are progressive conservative as much as they tend to secure feudal privileges for the nobility, yet from the aspect of the bourgeoisie's interest they appear to be a basis for the further development of capitalism. Contextualisation and political interpretation help dismantle a myth concerning the Magna Carta whereby the role of interests and power is exposed in creating the document while at the same time it implicitly reveals the complex relationship between law and politics in society. The authors of the Magna Carta did not intend to develop the legal instruments that emerged hundreds of years later when the rebellion against the feudal monarchy was led by the bourgeoisie and modern natural law included the idea of universal human rights.
Keywords: Lastnina; Magna Carta; Political interests; Political power; Politična moč; Politični interesi; Property; Velika listina svoboščin